Measurement and modelling of layered plasmonic structures - Shen, Mengqi (2018)
There are two main parts in this thesis: (1) to investigate a multi-layer structure that combines Kretschmann configuration and Otto configuration which we call the Kretschmann-Otto configuration. To examine this structure, we develop an objective based nano-controlled system; and (2) develop a transmission line model method to analyse the responsivity of surface plasmon (SP) sensors. In the first part, the Kretschmann-Otto structure is proposed and the performance of surface plasmon and Fabry-Perot modes formed in this structure is investigated. The motivation for this study is twofold, firstly, to look for modes that may be excited at lower incident angles compared to the usual Kretschmann configuration with similar or superior refractive index responsivity and, secondly, to develop a simple and applicable method to study these structures over a wide range of separations without recourse to the construction of ad hoc structures. With this nano-controlled system, we show that the contribution of gap separation to the minimum reflectivity and the width of reflected curve for the Otto configuration at visible wavelengths at a range of separations not reported hitherto. Moreover, the BFP distributions of Kretschmann-Otto configuration are investigated at various gap separations and the layer responsivity is demonstrated experimentally by fabricating a gold coated coverslip with a protein grating on top of it. We show that the zero order Fabry-Perot mode at normal incident angle has superior refractive index responsivity, by more than an order of magnitude, and layer responsivity by around 5 times compared to the Kretschmann configuration. In the second part, we propose a transmission line model based method to give insight into the sensing process and explain the main determinants to layer responsivity. By applying the appropriate resonant condition to the systems, we derive a circuit model which predicts the responsivity of different configurations. Specifically, the model provides a compact explanation for the change in responsivity due to a high index layer placed between the metal and the analyte. From this method, a parameter arises naturally from the model and the response of a generic sensor to binding of an analyte can be predicted. Intuitively, it may be expected that the energy stored in the circuit is related to the responsivity of the sensor, here we show that, under normal operating conditions, while it is predictive of the sharpness of the resonance the responsivity depends only on the variation of circuit reactance with wave number.